Notch intracellular domain overexpression in adipocytes confers lipodystrophy in mice - Dionysios V. Chartoumpekis; Dushani L. Palliyaguru; Nobunao Wakabayashi; Nicholas K.H. Khoo; Gabriele Schoiswohl; Robert M. O'Doherty; Thomas W. Kensler (Elsevier, 2015)
Objective: The Notch family of intermembrane receptors is highly conserved across species and is involved in cell fate and lineage control. Previous in vitro studies have shown that Notch may inhibit adipogenesis. Here we describe the role of Notch in adipose tissue by employing an in vivo murine model which overexpresses Notch in adipose tissue. Methods: Albino C57BL/6J RosaNICD/NICD::Adipoq-Cre (Ad-NICD) male mice were generated to overexpress the Notch intracellular domain (NICD) specifically in adipocytes. Male RosaNICD/NICD mice were used as controls. Mice were evaluated metabolically at the ages of 1 and 3 months by assessing body weights, serum metabolites, body composition (EchoMRI), glucose tolerance and insulin tolerance. Histological sections of adipose tissue depots as well as of liver were examined. The mRNA expression profile of genes involved in adipogenesis was analyzed by quantitative real-time PCR. Results: The Ad-NICD mice were heavier with significantly lower body fat mass compared to the controls. Small amounts of white adipose tissue could be seen in the 1-month old Ad-NICD mice, but was almost absent in the 3-months old mice. The Ad-NICD mice also had higher serum levels of glucose, insulin, triglyceride and non-esterified fatty acids. These differences were more prominent in the older (3-months) than in the younger (1-month) mice. The Ad-NICD mice also showed severe insulin resistance along with a steatotic liver. Gene expression analysis in the adipose tissue depots showed a significant repression of lipogenic (Fasn, Acacb) and adipogenic pathways (C/ebpα, C/ebpβ, Pparγ2, Srebf1). Conclusions: Increased Notch signaling in adipocytes in mice results in blocked expansion of white adipose tissue which leads to ectopic accumulation of lipids and insulin resistance, thus to a lipodystrophic phenotype. These results suggest that further investigation of the role of Notch signaling in adipocytes could lead to the manipulation of this pathway for therapeutic interventions in metabolic disease.